1995
DOI: 10.2105/ajph.85.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Heroin use during methadone maintenance treatment: the importance of methadone dose and cocaine use.

Abstract: OBJECTIVES. The purpose of this study was to examine factors associated with heroin use during methadone maintenance treatment. METHODS. Logistic regression statistical models were used to examine data obtained in a cross-sectional sample of 652 methadone patients. RESULTS. Heroin use during the 3 months prior to interview was shown to be greatest among (1) patients maintained on methadone dosages of less than 70 mg/day (adjusted odds ratio [OR] = 2.1, 95% confidence interval [CI] = 1.3, 3.4) and (2) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 33 publications
6
69
3
Order By: Relevance
“…Best et al (1998) reported alcohol prevalence rates between 20% and 50% in a group of individuals receiving methadone-maintenance treatment (Best et al, 1998). The prevalence of cocaine use found in the present study in methadonemaintained individuals was 11.11%, and this is notably lower than the prevalence reported in previous studies (Hartel et al, 1995;Magura et al, 1998;Grella et al, 1997), which indicated a prevalence of between 50% and 73%. A plausible explanation for this may be that adults living in mainly rural communities such as East Kent are expected to experience less use of Class A drugs than those living in urban areas.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Best et al (1998) reported alcohol prevalence rates between 20% and 50% in a group of individuals receiving methadone-maintenance treatment (Best et al, 1998). The prevalence of cocaine use found in the present study in methadonemaintained individuals was 11.11%, and this is notably lower than the prevalence reported in previous studies (Hartel et al, 1995;Magura et al, 1998;Grella et al, 1997), which indicated a prevalence of between 50% and 73%. A plausible explanation for this may be that adults living in mainly rural communities such as East Kent are expected to experience less use of Class A drugs than those living in urban areas.…”
Section: Discussioncontrasting
confidence: 80%
“…Despite this, the prevalence of cocaine use in methadone-maintained individuals in this study is not as high as reported in other studies conducted amongst such individuals. Some have reported values from 51.67% (Hartel et al, 1995) to 73% (Magura et al, 1998). This may be due to the factor explained above, namely that adults living in mainly rural communities such as East Kent are expected to experience less use of Class A drugs than those living in urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of methadone is limited, however, in individuals who are using cocaine, where it results in higher rates of heroin use and treatment dropout [12,19,21,37]. Considering that concurrent use of cocaine is widespread in methadone treatment programs, seen in almost 50% of patients [5,12,17,25], the impact of cocaine on the effectiveness of methadone is of central importance.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that concurrent use of cocaine is widespread in methadone treatment programs, seen in almost 50% of patients [5,12,17,25], the impact of cocaine on the effectiveness of methadone is of central importance. Similarly, a negative effect of concurrent use of cocaine has also been noted in individuals treated with buprenorphine [21,37].…”
Section: Introductionmentioning
confidence: 99%